Sedno sprawy: tertium datur. Kilka uwag o chrystologicznym wymiarze etyki Tadeusza Stycznia - SZYMIK, Jerzy (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
To the Rev. Tadeusz Styczeń, who died in October 2010, Christology was the “heart of the matter” not only in the existential but also in the scientific sense, including the methodological. This is the ethics−oriented Christology or Christologically−motivated ethics (with Christ−Truth as the source of freedom) practised at the Catholic University of Lublin as the heritage of Wojtyła’s–John Paul II’s teaching; this is erudite knowledge (drawing on many fields), wisdom transmitted in diverse forms, but frequently meditation based on Biblical exegesis. This is a profoundly incarnational Christology: Styczeń refers to the mystery of the Incarnation, reconciling anthropocentrism with theocentrism and, consequently, to the mystery of the Cross as an expression of solidarity with God and with man. Translated by Piotr Czyżewski